2000
DOI: 10.1007/bf02235565
|View full text |Cite
|
Sign up to set email alerts
|

Management of postoperative peritonitis after anterior resection

Abstract: Extensive intra-abdominal infection after anterior resection may be efficiently controlled by a surgical approach combining peritoneal debridement, fecal diversion, and capillary drainage of the pelvis. Intestinal continuity may be restored after diversion stoma or Hartmann's procedure after high anterior resection. This is not the case after a Hartmann's operation after a low colorectal anastomosis, and this procedure should be avoided whenever possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
9

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 24 publications
2
53
0
9
Order By: Relevance
“…Anastomotic insufficiency and postoperative ileus due to abdominal adhesions represent major complications following intestinal surgery, conditions associated with substantial morbidity and mortality 11 . We have previously shown that the combination of poly-L-lysine and poly-L-glutamate significantly reduces adhesions in an experimental model on abdominal adhesions 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Anastomotic insufficiency and postoperative ileus due to abdominal adhesions represent major complications following intestinal surgery, conditions associated with substantial morbidity and mortality 11 . We have previously shown that the combination of poly-L-lysine and poly-L-glutamate significantly reduces adhesions in an experimental model on abdominal adhesions 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Niska przednia resekcja odbytnicy, wykonywana również za pomocą staplerów, jest najlepszą metodą leczniczą w raku środ-kowej i dystalnej części odbytnicy. Przetoka w wykonanym zespoleniu jest najczęstszym i niebezpiecznym powikłaniem, może wystąpić w 3-15% zabiegów [12,14]. Obraz kliniczny jest dość niejednolity -od niewielkich miejscowych objawów z radiologicznym potwierdzeniem ograniczonego przecieku do gwałtownie narastającej sepsy w przebiegu ropnia czy ropni w jamie brzusznej lub objawów zapalenia otrzewnej.…”
Section: Epidemiologiaunclassified
“…Obraz kliniczny jest dość niejednolity -od niewielkich miejscowych objawów z radiologicznym potwierdzeniem ograniczonego przecieku do gwałtownie narastającej sepsy w przebiegu ropnia czy ropni w jamie brzusznej lub objawów zapalenia otrzewnej. Śmiertelność w przypadkach przetoki z objawami zapalenia otrzewnej jest duża, sięga nawet 50% [12][13][14]. Sytuacja taka wymaga doraźnych zabiegów ratujących życie pacjenta.…”
Section: Epidemiologiaunclassified
See 2 more Smart Citations